1983
DOI: 10.1007/bf01257312
|View full text |Cite
|
Sign up to set email alerts
|

Experimentelle Gallensteinbildung. �tiologische Bedeutung von?-Glucuronidase-bildenden Bakterien und Gallenwegsobstruktionen

Abstract: Bile pigment gallstones were produced in six of six mongrel dogs by narrowing the cystic duct with ligature after a postoperative interval of seven days. beta-Glucuronidase producing group G Streptococcus and Staphylococcus aureus were found in the bile, the gallbladder wall, and the liver. In another trial similar gallstones were produced in four of eight dogs after mere injection of beta-glucuronidase producing Escherichia coli into the spleen resp. in six of eight dogs after injection of E. coli into the co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0
3

Year Published

1984
1984
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 17 publications
0
4
0
3
Order By: Relevance
“…Another study indicated that the model could be established in mongrel dogs via injection of b-glucuronidase-producing Escherichia coli into the spleen, or by narrowing the bile duct with ligature after a 7-day post-operative interval. [21] Furthermore, hypodermic injection of lincomycin also reportedly induces pigment gallstone formation in guinea pigs. [22] In our study, we established a brown pigment stone rat model which we induced through a modified LD, with protein content (12%) far lower than in the CD (21%).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another study indicated that the model could be established in mongrel dogs via injection of b-glucuronidase-producing Escherichia coli into the spleen, or by narrowing the bile duct with ligature after a 7-day post-operative interval. [21] Furthermore, hypodermic injection of lincomycin also reportedly induces pigment gallstone formation in guinea pigs. [22] In our study, we established a brown pigment stone rat model which we induced through a modified LD, with protein content (12%) far lower than in the CD (21%).…”
Section: Discussionmentioning
confidence: 99%
“…A previous study by Suzuki et al [20] reported that a pigment gallstone rat model could be established through a low protein diet, resulting in incomplete obstruction of the terminal common bile duct. Another study indicated that the model could be established in mongrel dogs via injection of β-glucuronidase-producing Escherichia coli into the spleen, or by narrowing the bile duct with ligature after a 7-day post-operative interval [21] . Furthermore, hypodermic injection of lincomycin also reportedly induces pigment gallstone formation in guinea pigs [22] .…”
Section: Discussionmentioning
confidence: 99%
“…Die Anziichtung und Identifizierung der Bakterien erfolgte nach den friiher angegebenen Methoden [8]. Nach Cholecystektomie wurden die Gallenflfissigkeit, die Gallenblasenwand und die Gallensteine mit mikrobiologischen Methoden auf ihren Gehalt an Bakterien untersucht.…”
Section: Patienten Und Methodenunclassified
“…Die vorliegenden Ergebnisse bestfitigen frfihere klinische und experimentelle Untersuchungen, nach denen bei Gallensteintrfigern nicht nur die Gallenflfissigkeit, sondern auch die Gallenblasenwand und die Gallensteine bakteriell besiedelt sein k6nnen [1,4,8,12]. Ob die Bakterien in der Gallenblasenwand sogar hfiufiger sind als in der Galle, muB often blciben, da ein statistisch signifikanter Unterschied nicht vorhanden war.…”
Section: Diskussionunclassified
See 1 more Smart Citation